Development of a numeracy literacy ability test instrument based on high order thinking skills (hots) in junior high school mathematics learning - Arriah, Fathrul; Romba, Sri Sufliati (Universitas Islam Negeri Raden Intan Lampung, 2023)
The aim of this study was to develop a numeracy literacy test instrument based on the High Order Thinking Skills (HOTS) for class VIII junior high school students. The type of research used is research and development (R&D) with the ADDIE model. The ADDIE model consists of five stages of development, namely: Analysis, Design, Development, Implementation, and Evaluation. A total of 15 questions have been prepared covering the material for straight line equations, functions, coordinate systems, linear equations of two variables and number patterns in odd semesters. The items were validated by three mathematicians, and the calculations were analyzed using the Aiken index. Furthermore, the questions that were declared valid were tested on 34 students in two junior high schools in Makassar City using convenience sampling as a sample selection technique. The experimental data are dichotomous. The data were analyzed using KR-20 to produce a reliability coefficient. This study resulted in a HOTS-based numeric literacy test instrument in the form of multiple choice with a total of 15 valid and reliable questions. 15 items have high category validity, while the reliability coefficient of the item is 0.91, or high category.